Pandangan Dunia Kahlil Gibran dalam Novel Sayap-Sayap Patah - Fuad, Akhmad Dzukaul; Dermawan, Taufik (Universitas Muhammadiyah Jember, 2022)
The structure of the novel broken wings consists of ten parts that describe the stages of the